Strategi Kampanye Inovasi Jatim Bersih dan Lestari (Berseri) Provinsi Jawa Timur Melalui Kanal Youtube dalam Rangka Mewujudkan Jatim Zero Waste - Nuruddin Nuruddin; Nuril Ahmad (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
The problem of waste has become a global issue that is still looking for effective and efficient solutions to reduce it. East Java has a population of 42.09 million. The waste produced annually is 6.8 million tons, while the amount managed reaches 3.8 million tons. The East Java Provincial Government through the Environmental Service (DLH) has provided positive education to the community through the Clean and Sustainable East Java Innovation (Berseri). This innovation is in the form of a competition for the utilization of recycled waste that has economic value and creates a culture of clean and healthy living in all villages in East Java. The research method used is qualitative with a descriptive narrative approach used to analyze the action strategy of the East Java Provincial Government’s DLH in reducing waste. This study found a positive impact through the creation of educational recycling videos uploaded to the YouTube platform. The East Java Provincial Government’s DLH invites, massive socialization not only for East Java but also to all viewers around the world.